The city on the hill from below : the crisis of prophetic Black politics - Marshall, Stephen H. (Temple University Press, 2011)
Within the discipline of American political science and the field of political theory, African American prophetic political critique as a form of political theorizing has been largely neglected. Stephen Marshall, in The City on the Hill from Below, interrogates the political thought of David Walker, Frederick Douglass, W.E.B. DuBois, James Baldwin, and Toni Morrison to reveal a vital tradition of American political theorizing and engagement with an American political imaginary forged by the City on the Hill. Originally articulated to describe colonial settlement, state formation, and national.